Body and appearance self-conscious emotions in Canada and Poland. (September 2021) - Razmus, Magdalena; Razmus, Wiktor; Castonguay, Andree L; Sabiston, Catherine M
Due to the growing interest in studies on health-related variables from an international perspective, the current study addresses the issue of body-related emotions in two countries from two continents, namely, North America and Europe. Using data from Canadian and Polish samples, we investigated the cross-cultural measurement invariance of the Body and Appearance Self-Conscious Emotions Scale across countries and examined differences in these emotions between Canada and Poland. Partial scalar invariance indicated that the scale functions equivalently in Canadian and Polish samples, with only one invariant item in the Guilt subscale. Compared to the Polish, Canadians reported lower body and appearance authentic and hubristic pride. Participants from the two countries did not differ significantly in shame.